Implementasi Pendekatan Saintifik dalam Pembelajaran SKI di MA As Shofa Jember - Bahrul Munib; Kurnia Firdausy Komala; Syed Iftikhar Ali Gilani (Yayasan Azhar Amanaa Yogyakarta, 2023)
In a learning approach process it greatly influence the effectiveness of teacing which also determines the success of learning. To produce active, critical, innovative student, changes are needed this a learning. The changes made in a learing process are using the right approach, namely the scientific. The focus of research in this is how is to analyze and describe implementation of scientific approach to the learning process of Islamic cultural histiory for class x at Madrasah Aliyah As Shofa. To analyze and describe evaluation and obstacles in the learing Islamic culture history. This study used a qualitative descriptive type approach. Data colection techniques used participation observation, semi structure interviews and documentation. Data analysis used the interactive model Miles Huberman and Saldana which includes three steps: data kondetation, data presentation, conclusion drawing and verification. The validity of the data use source triangulation and technique trangulation this recearch draws coclution 1). in the early stages off planing by making a learning implementation plan (RPP). Throught several step commonly calleds 5M (Observing, Asking, Gathering Informatio, reasoning comunication ), 2). Obstcles encoutered in the sceintific approach to this learing process of Islamic cultural history, 1) in observing activites new student need adjustment, 2) in the activity of asking embbarasment in submiting question, 3) in the activity of gathering information low interesting in reading, 4) in the activity reasoning , they lack mastery of the material and tend to be paasive, 5) in the activity of comunicating Islamis cultural history material too broad. Evaluation of Islamis cultural history is use three evaluation namely evaluation cognitive domain which is carried out throught oral and the written test activities, evaluation afective domain throught observation sheets of attitude and behaviour, and evaluation psychomotor domain throught comunication practice activities in front off the class